2017
DOI: 10.1108/ijppm-11-2015-0168
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between sustainable operations practices and performance: a meta-analysis

Abstract: Purpose The purpose of this paper is to examine the relationship between sustainable operations practices (SOP) and performance. Design/methodology/approach This study was conducted through a systematic literature review followed by a meta-analysis of correlations. Findings In the results, 14 of the relationships examined showed a positive relationship and 12 the presence of moderators. The study findings indicate that contingency affects the relationship between SOPs and performance. Research limitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 104 publications
2
20
0
2
Order By: Relevance
“…Moreover, many definitions overlap with other concepts such as, among others, robustness, fault-tolerance, flexibility, survivability, and agility [2]. Engineering resilience draws attention to the ability of a resilient system to return to its pre-disturbance state as quickly as possible [14], implying a focus on efficiency of function [15]. It contributes to organizational resilience, which focus on the adaptive capacity of the organizations and is a dynamic process that implies the ability of developing capabilities to face new situations [13].…”
Section: Resilience Sustainability and Firms' Performance Relationship: An Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, many definitions overlap with other concepts such as, among others, robustness, fault-tolerance, flexibility, survivability, and agility [2]. Engineering resilience draws attention to the ability of a resilient system to return to its pre-disturbance state as quickly as possible [14], implying a focus on efficiency of function [15]. It contributes to organizational resilience, which focus on the adaptive capacity of the organizations and is a dynamic process that implies the ability of developing capabilities to face new situations [13].…”
Section: Resilience Sustainability and Firms' Performance Relationship: An Overviewmentioning
confidence: 99%
“…In addition, the industry sector, firm size or the examined market seem to impact on the results. A meta-analysis of the correlations between sustainable operations practices (SOP) and firms' performance has been performed by D'Agostini et al [14]. In the study, after a systematic literature review, 15 selected SOP are compared with environmental, economic, operational and organizational performance.…”
Section: Resilience Sustainability and Firms' Performance Relationship: An Overviewmentioning
confidence: 99%
“…It should be noted that the use of environmental practices, such as cleaner production, has a positive relationship with OP. It shows that an organization with robust cleaner production practices stands out in the market in comparison to the competition (D’Agostini et al , 2017). De Sousa Jabbour et al (2015) indicated that if a company intends to improve environmental performance, it can create procedures and programs based on the environmental management system and can adopt cleaner production initiatives for superior performance.…”
Section: Sustainable Operationsmentioning
confidence: 99%
“…Thus, the introduction of sustainable and green measures can be crucial for the OGS. Environmental sustainability is frequently operationalized as a small group of measurable objectives in organizational inputs and outputs, such as lowering energy consumption, reutilizing or reducing waste, and minimizing carbon dioxide emissions (Brooks et al, 2012;D'Agostini, 2017;Ferreira and Pernici, 2016). O&G companies tend to view social and environmental management as partly a voluntary approach and usually dependent on leadership and culture (Tomlinson, 2017).…”
Section: Introductionmentioning
confidence: 99%